The use of protocols in emergency and emergency units: an integrative review - Degasperi, Alana (2020)
The urgency and emergency care protocols serve as guides for professionals to provide qualified, organized and more humanized care to patients who seek institutions for care. The objective of the study was to analyze scientific productions regarding urgency and emergency care protocols in hospital units in the national context, analyzing and evidencing the available material on the subject presented. This is a descriptive integrative literature review. The search for scientific articles was carried out in the SciELO database, using the terms "Nursing protocols", "Urgency" and "Emergency", in all fields, and "Nursing" in the area of knowledge. The results of the study revealed the importance of using the assignments of urgency and emergency protocols in hospital units, serving as assistance guides for health professionals, providing them with more security in the execution of the task. The study is concluded by highlighting the scarcity of publications on the topic for the scientific attributions in the study and highlighting the importance of nurses in front of the nursing team for the execution of tasks as a form of sector management and coordination.